Frames of Coverage of the Daniel Hurricane Disaster in Derna, Libya by the Website of Al-Sharq Al-Awsat International Newspaper: An Analytical Study from 10/9/2023 to 30/11/2023 - Atbiqa, Abdullah Mohammed; Al-Ajm, Muhammad Abdullah; Al-Shaibani, Salah Muhammad (ALBAHITH ALALAMI, 2024)
The research problem is centered around the main question: What are the coverage frames used by the website of Al-Sharq Al-Awsat International newspaper for the Daniel Hurricane disaster in Derna, Libya? This study falls within descriptive-analytical research, using content analysis applied to a readily available sample of news articles on the Al-Sharq Al-Awsat website regarding the Daniel Hurricane disaster in Derna, Libya. The period of analysis covered from September 10, 2023, to November 30, 2023, during which 142 news articles were analyzed. The researchers used a content analysis form as the main research tool. The study revealed several findings, including: Derna is the most affected region by the Daniel Hurricane in Libya, according to the Al-Sharq Al-Awsat website, with a coverage rate of 39.4%. Journalists were the most frequently cited sources in the coverage of the disaster, contributing to 40.9% of the content. The Libyan National Army’s General Command was the most prominently featured entity among the active forces mentioned in the news articles, appearing in 24.5% of the coverage.